Microstrip Wireless Antenna Used By Capsule For Stomach Internal Photography - Mayss Alreem Nizar Hammed; Rashid Ali Fayadh (Journal of Techniques)
a wireless capsule endoscopy is small device used to examine the digestive system. The big challenge in the development of the capsule is how to get high date rate and also reduce the size of the capsule so micro strip antenna has been used which has several advantages such as small size, light weight, low cost. In this paper, UWB mini polygonal slotted patch antenna has been designed which has overall size of 10 X 10mm and bandwidth of 6GHz (5.5 – 11.5 GHz) .The simulation results for return loss (S11) has -26.32 at 6.6 GHz and voltage standing wave ratio (VSWR) at 1.09. The simulated radiation patterns are Omni-directional radiations over the UWB bandwidth.